Pelaksanaan Pendidikan Sistem Ganda SMK Teknologi Jurusan Bangunan di Dunia Usaha Jasa Konstruksi - Tri Kuncoro; Made Wena; Priyono Priyono; Isnandar Isnandar (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1998)
The Implementation of Dual System of Education by Civil Department of Secondary School of Technology at Construction Business. To Civil Department of Secondary School of Technology, the implementation of the dual system of education (PSG) is intended to utilize the business potentials in optimalizing the students’ potentials. This descriptive-evaluative study was designed to describe the planning, implementation, and evaluation of the PSG, and the obstacles in implementing the program. The subjects were 20 teacher-advisors, 30 instructors, and 60 students, who were randomly sampled from the population in East Java. The results of qualitative and quantitative data analysis showed that the planning, implementation, and evaluation of the PSG were not satisfactory yet. One of the obstacles was the limited equipment and material for practical work.